Understanding Anticonsumption in Tourism Services: A Qualitative Study of Young Slovenian Travelers - Rakuša, Nika; Milfelner, Borut (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This research aims to explore how anticonsumption manifests in tourism, specifically among young Slovenian consumers. It addresses a gap in the literature, which often focuses on promoting sustainable products while overlooking the reasons behind anticonsumption in the tourism and service sectors (Garima et al., 2024). The study highlights the disparity between sustainable attitudes and actual vacation behaviours (Nikolić et al., 2021). Using a qualitative approach, the methodology includes conducting a focus group with young adults to identify motivations for and against anticonsumption in tourism (Liu-Lastres et al., 2025). The research will also examine psychological mechanisms like moral disengagement (Pizzetti et al., 2024) and guilt (Mkono & Hughes, 2020), as well as cultural factors relevant to Slovenia (Krsnik & Erjavec, 2024). The collected data will undergo content analysis and coding to provide deeper insights. Expected findings include key motives influencing anticonsumption behaviour and why sustainable practices often fall short in vacation settings. This research aims to clarify how participants rationalize their decisions. The findings will help marketing professionals develop credible, sustainable strategies and adapt offerings that promote responsible vacation behaviours.